Comparative microfluidic and enzymatic analyses reveal multifaceted snake venom resistance and novel VWF behavior in the opossum Monodelphis domestica - Matthew L. Holding; Dante Disharoon; Laura M. Haynes; Bipin Chakravarthy Paruchuri; M. Hao Hao Pontius; Krista Golden; Jordan A. Shavit; Karl C. Desch; David Ginsburg; Anirban Sen Gupta; Yolanda Cruz; Danielle H. Drabeck (PLoS ONE, 2025)
Interactions between predators and prey are often characterized by strong selection pressures that shape extreme physiological adaptations. Venom resistance in large-bodied South American opossums (Clade Didelphini) is a striking example, as these marsupials prey on venomous snakes and exhibit remarkable resistance to their venom. While resistance is well documented in Didelphini, relatively little is known about venom resistance in the smaller, more diverse members of Didelphidae, which inhabit the same regions and encounter the same predators. Moreover, resistance of opossum von Willebrand factor (VWF) to the venom C-type lectin-like proteins has not been previously studied under simulated vascular flow states. Here, we use microfluidic devices to investigate venom resistance in the small-bodied opossum, Monodelphis domestica, examining platelet adhesion and fibrin deposition in response to purified venom components. Additionally, we conduct platelet aggregometry and assays of serum protease inhibitors in the presence of venom from sympatric and allopatric vipers to examine patterns of species-specificity and adaptation. Our results show that M. domestica resists venom-induced disruptions to platelet function in the presence of platelet-disrupting venom components botrocetin and convulxin, while aspercetin disrupts platelet and fibrin function similarly in opossum and human samples. Whole blood aggregometry and serum protease inhibition showed patterns consistent with species-specific adaptation of mammals to their local snake venom. Unexpectedly, we find that M. domestica VWF requires increased shear force to elongate, a previously unknown aspect of opossum blood physiology that may contribute to venom resistance and may have relevance to human coagulopathies. Our findings demonstrate resistance under natural shear stress, and document venom resistance beyond large-bodied Didelphini, suggesting it is a widespread trait in South American marsupials.